Answer:
Option 4, 64 cm^2
Step-by-step explanation:
The polygon in the shape of a star can be made to be easier to find the area of by cutting it into triangle. For all the "point edges" of the star, we can cut them in half from the vertex to create two right-angled triangles at each edge.
The formula of the area of a triangle is bh/2: the height is given as 6cm, the base is 4cm /2 (after you cut it in half) and so is 2 cm. Since the edges can be cut into two, there are 8 right angled triangles at the edges in total.
To find the area of them:
A=8(bh/2)=8(2*6/2)=48 cm^2
However, we are still missing the part at the centre we haven't found the area of, the square. The area of a square is given by the square of the side length(4cm). Thus, A=4*4=16cm^2
Adding the areas of all the edges and the square:
48 + 16 = 64cm^2
Hence, the area of the polygon is 64cm^2
Answer:
$11,000
Step-by-step explanation:
275,000×4% = 11,000
Answer:
Combinations:
A committee consisting of three members with the same role
Selecting two sandwiches from a menu of 10
Step-by-step explanation:
A combination is a selection of items from a collection, such that the order of selection does not matter.
A permutation is a selection of items from a collection, such that the order of selection matters.
A. The PIN for a bank or credit card - order matters → permutation
B. A committee consisting of three members with the same role - order does not matter → combination
C. A committee consisting of a president, vice president, and secretary - order matters → permutation
D. Final standings in a professional sports league - order matters → permutation
E. Selecting two sandwiches from a menu of 10 - order does not matter → combination
Step-by-step explanation:
<em>x² - x - 20 = 0</em>
<em>x²</em><em> </em><em>-</em><em> </em><em>(</em><em>5</em><em>-</em><em>4</em><em>)</em><em> </em><em>x </em><em>-</em><em> </em><em>2</em><em>0</em><em> </em><em>=</em><em> </em><em>0</em><em> </em>
<em>x²</em><em> </em><em>-</em><em> </em><em>5x </em><em>+</em><em> </em><em>4x </em><em>-</em><em>2</em><em>0</em><em> </em><em>=</em><em> </em><em>0</em>
<em>x </em><em>(</em><em> </em><em>x </em><em>-</em><em> </em><em>5</em><em>)</em><em> </em><em>+</em><em> </em><em>4</em><em> </em><em>(</em><em> </em><em>x </em><em>-</em><em> </em><em>5</em><em>)</em><em> </em><em>=</em><em> </em><em>0</em>
<em>(</em><em>x </em><em>-</em><em> </em><em>5</em><em>)</em><em> </em><em>(</em><em>x+</em><em> </em><em>4)</em><em> </em><em>=</em><em> </em><em>0</em>
<em>Either</em><em>. </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em>
<em>x </em><em>-</em><em> </em><em>5</em><em> </em><em>=</em><em> </em><em>0</em>
<em>x </em><em>=</em><em> </em><em>5</em>
<em>Or, </em>
<em>x </em><em>+</em><em> </em><em>4</em><em> </em><em>=</em><em> </em><em>0</em><em> </em>
<em>x </em><em>=</em><em> </em><em>-</em><em>4</em>